Prevalence of Various Traumatic Events Including Sexual Trauma in a Clinical Sample of Patients With an Eating Disorder - Kjaersdam Telléus, Gry; Lauritsen, Marlene Briciet; Rodrigo-Domingo, Maria (Frontiers in Psychology, 2021)
Objective: Eating disorder (ED) and trauma have often been associated, and there is evidence that early experiences of traumatic events are associated with subsequent ED. Research results point towards an increased prevalence of sexual trauma in individuals with ED, and it has been suggested that sexual trauma precedes and contributes to the development of ED. The aim of this study was to assess the prevalence of sexual trauma as well as other types of traumatic life events in a clinical sample of children, adolescents and adults with ED. Method: Patients (N=329), median age 16.9 (Interquartile Range (IQR):4.5), diagnosed with various EDs in a specialized ED unit were included. Results: The majority (67%) of patients with ED reported at least one traumatic life event at time of assessment such as bullying (32%), loss (24%), or accidents (11%). Nineteen per cent of the patients reported having been the victim of a sexual trauma or another sexual traumatic event distributed as follows in terms of severity: 13% had been the victim of a negative experience associated with sex; 57% reported having experienced sexual assault other than rape; and 30% had been the victim of severe forms of sexual assault. The median time between the sexual trauma and the ED diagnosis was 3.4 years (IQR: 6.6). The median time between the sexual trauma and the onset of ED symptoms was 0 years (IQR: 5). The study results imply that the sexual trauma could be experienced either prior to or after onset of ED symptoms. Conclusions: Sixty-seven per cent of the patients with an ED reported traumatic life events at time of assessment, whereby 19% reporting negative sexual experiences or sexual abuse. However, sexual trauma does not necessarily play a causal role in the development of EDs.